COMBINED BIOLOGICAL AND CHEMICAL TREATMENT OF HIGH-STRENGTH YEAST PROCESSING EFFLUENT - MANHOKWE, SHEPHERD (Midlands State University, 2022)
The main objective of this thesis was to investigate the feasibility of wastewater treatment using a combined biological and chemical treatment system for effluent from a yeast processing plant in Zimbabwe. The initial phase of this study involved a survey aimed at identifying and noting the current practices and experiences of food industrial wastewater treatment in Zimbabwe. The survey revealed that about 86 % of the food processing industries surveyed made use of primary treatment facilities with only 9 % having biological treatment facilities. Wastewater was characterised for Chemical Oxygen Demand (COD), phosphates, pH, sulphates, Total Dissolved Solids (TDS) and conductivity. High COD values were recorded in yeast processing effluent (3097 mg/L) and all the effluents assessed had COD values above the recommended regulatory limit of 60 mg/L. The second phase of the research was to study the interactive effects of temperature and bacteria in the treatment of the yeast processing effluent. The objective was to optimize the operating parameters that reduce organic load and colour. Biological treatment was conducted using Response Surface Methodology (RSM) and a Central Composite Design (CCD) was used to determine optimum conditions on Design Expert 7 software. Two dependent variables namely, COD reduction and colour reductions were studied. COD removal efficiency of 26% and decolourization efficiency of 44% were recorded during the wastewater treatment. The optimised conditions for the biological treatment were found to be effective when the bacterial culture load was at 16.37 g/L at 25 °C for both COD and colour reduction. The research further went on to assess the feasibility of anaerobic treatment of yeast processing effluent using an Upflow Anaerobic Sludge Bed (UASB) reactor at various temperatures. Physico-chemical measurements for Total Dissolved Solids (TDS), pH, Volatile Fatty Acids (VFAs) and COD were done. The analysis of VFAs in the UASB anaerobic digester was done using an Ultra High-Performance Liquid Chromatography (UHPLC). Trace metal ion concentration was determined using Inductively Coupled Plasma (ICP-AES). It was interesting to note a drastic change in the COD reduction that varied from 32.67% at 40 oC to 19.12% at thermophilic temperature of 50 oC. However, at 45 oC biogas production was at maximum, with an average of 0.031 m3CH4 m−3d−1. VFAs recorded in the bioreactor were 2743 ppm and 1326 ppm for acetic and propionic acid respectively. Post-treatment process under laboratory scale using coagulation/flocculation process was done for the reduction of colour, turbidity and COD in biologically treated effluent. The combination of semi‐continuous UASB biological reactor treatment was followed by a post-treatment process using aluminium chlorohydrate polyadamac as a coagulant. Thermogravimetric analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR) analysis of the sludge was also done to ascertain the characteristics of the flocs. The highest treatment efficiencies for COD reduction and colour removal were 63.63% and 68.25% respectively at pH 6. A turbidity reduction of 91.33 % was observed in this study. The thermogravimetric behaviour of the sludge was noted with loss of moisture and other volatile organic acids. FTIR analysis showed the presence of more functional groups in the coagulation residue than the coagulant. Morphological and biochemical tests were performed to differentiate the isolates and 27 bacterial isolates were identified. Further identification and verification was done using Matrix Assisted Laser Desorption Ionisation-Time of Flight Mass Spectrometry (MALDI-TOF MS). Five species were predominantly found in raw yeast processing effluent that included; Bacillus cereus, Proteus vulgaris, Lysinibacillus sphaericus, Ochrobactrum intermedium and Providencia rettgeri. In treated wastewater, Alcaligenes faecalis, Serratia liquiefaciens Brevundimonas diminuta and Bacillus cereus species were isolated and identified. The results, in this study, indicate the feasibility of combined treatment of yeast processing wastewater. The combined biological and chemical treatment is suitable for the removal of organic load and colour from wastewater as well as generation of biogas.